Pengaruh persepsi wajib pajak dan sanksi denda terhadap kepatuhan pajak kendaraan bermotor (Undang-undang LLAJ No. 22, 2009) - Annisa Mutiara Pratiwi; Whereson Siringoringo (JAAF (Journal of Applied Accounting and Finance), 2023)
The research aims to determine taxpayer’s perception regarding the implementation of traffic and road transportation law No. 22 of 2009, specifically article 74, paragraphs (2) and (3), which pertain to the deletion of motor vehicle identity data and fines for motor vehicle taxpayer compliance in Bekasi regency. This study employs a quantitative approach with the population consisting of motor vehicle taxpayers registered at the Bekasi regency samsat office. A non-probability sampling method is used with a sample size of 160 respondents, and data collection is conducted through questionnaires. The data analysis method employed is multiple linear regression with the assistance of SPSS version 24 software. The research results indicate that taxpayers' perceptions of the implementation of traffic and road transportation law No. 22 of 2009, article 74, paragraphs (2) and (3), significantly influence motor vehicle taxpayer compliance, and fine sanctions also have a significant impact on motor vehicle taxpayer compliance.